Serum Insulin-Like Growth Factor I Deficiency Associates to Alzheimer's Disease Co-Morbidities - Zegarra-Valdivia, JA (2019)
We are thankful to M. Garcia for technical support. This work was funded by a grant from Ciberned, by and Inter-CIBER project (PIE14/00061), and from SAF2016-76462-C2-1-P (MINECO). J.A. ZegarraValdivia acknowledges the financial support from the National Council of Science, Technology and Technological Innovation (CONCYTEC, Peru) through ´the National Fund for Scientific and Technological Development (FONDECYT, Peru). ´Authors’ disclosures available online (https://www.j-alz.com/manuscript-disclosures/19-0241).